?-Fluoro-Benzylphosphonates as Reagents for the Preparation of 1-Fluoro-1-Aryl Alkenes and ?-Fluorostilbenes - Thomas Allmendinger; Roger Fujimoto; Fabrizio Gasparini; Walter Schilling; Yoshi Satoh (CHIMIA, 2004)
The preparation of several fluoro-benzylphosphonates Ar-CHF-PO(OEt)2 and their Wadsworth-Emmons type olefination with aldehydes and ketones are described affording fluorostyrenes and fluorostilbenes. Some of these compounds are incorporated into target molecules tested as drug candidates.